Penerapan Strategi Dakwah Sentimental Dalam Memotivasi Minat Baca Al-Qur’an Jamaah Majelis Taklim Tomaupa Desa Lampoko Kecamatan Campalagian Kabupaten Polewali Mandar - Raudhatul Jannah H. Rahman; Nurhidayat M. Said; St. Aisyah BM (Hikmah, 2026)
The main problem in this study is how the process of implementing the sentimental da'wah strategy in motivating the congregation's interest in reading the Qur'an in the Qur'an learning activities at the Tomaupa Taklim Assembly. This type of research is field research with a qualitative approach. The methodological approach used is the communication science approach. The primary data sources of this study are the supervisor of the Tomaupa Taklim Assembly, the chairman of the taklim assembly, the secretary of the Campalagian District BKMT, community leaders of Lampoko Village, and the congregation of the Tomaupa Taklim Assembly. Data collection techniques were carried out through observation, interviews, documentation, and reference searches, while data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the process of implementing the sentimental da'wah strategy at the Tomaupa Taklim Assembly was implemented through a personal and family approach, providing spiritual motivation about the virtues of the Qur'an, and persuasive coaching that was carried out patiently, continuously, and adapted to the characteristics of the congregation. The implementation of this strategy has resulted in increased congregational engagement in learning, improved Quranic reading skills, and the formation of independent Quranic reading habits. Furthermore, this strategy has had a tangible impact on the community, marked by increased congregational participation in religious activities, growing community trust in the congregation to lead worship activities, and an increased role for the congregation in fostering a religious atmosphere within the family.